Emailing in English Writing: a Case Study Towards Students in Two Classes at SMA Negeri 1 Sinjai - Meta Mutiamiftah; Haryanto Atmowardoyo; Baso Jabu (Universitas Negeri Makassar, 2018)
This article explores the reasons of the students for emailing activities and how emailing activities influence the student’ writing competence. It also discusses emailing support the students writing competence at SMA Neg 1 Sinjai. This article applied a qualitative method, covering the collection, analysis, and interpretation of comprehensive narrative and visual data in order to gain insights into a particular phenomenon of interest. The participants of this article were the second year students of SMA Negeri 1 Sinjai, consisting of 10 students chosen from two classes using purposive sampling. The data of this research were collected through observation with simple protocol. The data were analyzed using the grounded theory technique, including three types or stages of data analysis:l open coding, axial coding, and selective coding.The result of this research reveals the student’s reasons for emailing activities, that is because it is interesting to do, comfortable, fast, and usable to send many file. Then, raising the habit of using English language when writing in email, improves their writing competence. And the English teacher claims that email as a learning tool is beneficial in increasing the students gradesin English language subject.